Hunting nature : Ivan Turgenev and the organic world - Hodge, Thomas P. (Cornell University Press, 2020)
"When we take seriously the effect Ivan Turgenev's lifelong passion for hunting had on his literary craft, we dramatically deepen our appreciation of the rich and complex ways one of Russia's most beloved writers depicted the natural world and the place of human beings within it"--